Obesity and Non Communicable Risk Factors for Hypertension a Population-Based Cross-Sectional Study - Beya Idrees, Ali Bin Waseem, Hasaan Ullah Khan, Kainat Bakhtiar, Insha Noor Al Majid, Muhammad Suleman Babar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hypertension is very common in both men and women in all over the world, according to several studies, obesity, smoking, and physical inactivity are causative factors for hypertensive men and women. Conclusion: The finding of the current study described that obesity and overweight and non-communicable factors such as smoking, inactive lifestyle, unbalanced diet, use of alcohol have direct correlation with systolic and diastolic blood pressure of individuals. Keywords: obesity, overweight, non-communicable factors, smoking, inactive lifestyle, unbalanced diet, systolic and diastolic blood pressure of individuals.